Vitamin C promotes oligodendrocytes generation and remyelination. Issue 7 (9th February 2018) - Guo, Yu‐e; Suo, Na; Cui, Xue; Yuan, Qianting; Xie, Xin
Abstract: Oligodendrocyte‐formed myelin sheaths play important roles in the neuronal functions in the central nervous system. In demyelinating diseases, such as Multiple Sclerosis, the myelin sheaths are damaged and the remyelinating process is somehow hindered. Restoration of the myelin sheaths requires the differentiation of the oligodendrocyte precursor cells (OPCs) into mature oligodendrocytes (OLs). To discover small molecule compounds that might promote the OPC to OL differentiation, a high‐throughput screening system is established and L‐ascorbyl‐2‐phosphate (As‐2P), a stable form of Vitamin C (Vc), is found to greatly enhance the OPC to OL differentiation. As‐2P promotes gradual expression of OL lineage markers, including O4, CNPase and MBP, in a dose‐ and time‐dependent manner. It also facilitates the formation of myelin sheaths in OPC‐neuron co‐culture. As‐2P also promotes the repair of the myelin sheaths in vivo and provides significant therapeutic effect in a cuprizone‐mediated demyelination animal model. Interestingly, As‐2P's function in promoting OPC differentiation is not related to its antioxidant activity. And an intracellular rather than an extracellular mechanism might be involved. Considering the safe use of Vc as a dietary supplement for many years, it might also be used as an alternative medicine for CNS demyelinating diseases. Main Points: As‐2P, a stable form of Vitamin C, promotes oligodendrocyte differentiation. As‐2P promotes myelin formation both in vitro and in vivo. SVCT2 mediates As‐2P's effect in oligodendrocyte differentiation.